Controllable Electrochemical Synthesis of Silver Nanoparticles on Indium‐Tin‐Oxide‐Coated Glass. Issue 4 (11th February 2015) - Yan, Ziren; Peng, Yang; Wu, Ying; Di, Junwei
Abstract A simple electrochemical approach, which integrates nanoseed nucleation and a square‐wave cyclic voltammetry (SWCV) growth strategy, was developed to construct silver nanoparticles (AgNPs) on indium tin oxide (ITO)‐coated glass surfaces. Ag nanoseeds were first deposited on the ITO surface by using pulse chronoamperometry and the particles were then grown during the SWCV process. Factors that have great effects on the characterization of AgNPs during the electrochemical process were systematically investigated. It is demonstrated that the growth process can be controlled separately. AgNPs and clusters were deposited and grown onto the ITO substrate. Moreover, the nanoparticles grew monotonically with increasing number of cycles, which provides a powerful tool to control the nanoparticle size by simply changing the number of SWCV cycles.